3D bioprinting for musculoskeletal applications. Issue 3 (July 2017) - Popov, Alexander; Malferrari, Sara; Kalaskar, Deepak M
This review focuses on developments in the field of bioprinting for musculoskeletal tissue engineering, along with discussion on the various approaches for bone, cartilage and connective tissue fabrication. All approaches (cell-laden, cell-free and a combination of both) aim to obtain complex, living tissues able to develop and mature, using the same fundamental technology. To date, co-printing of cell-laden and cell-free materials has been revealed to be the most promising approach for musculoskeletal applications because materials with good bioactivity and good mechanical strength can be combined within the same constructs. Bioprinting for musculoskeletal applications is a developing field, and detailed discussion on the current challenges and future perspectives is also presented in this review.